Brain-derived neurotrophic factor: a bridge between inflammation and neuroplasticity - Calabrese, Francesca; Rossetti, Andrea C.; Racagni, Giorgio; Gass, Peter; Riva, Marco A.; Molteni, Raffaella (Frontiers in Cellular Neuroscience, 2014)
Cytokines are key regulatory mediators involved in the host response to immunological challenges, but also play a critical role in the communication between the immune and the central nervous system. For this, their expression in both systems is under a tight regulatory control. However, pathological conditions may lead to an overproduction of pro-inflammatory cytokines that may have a detrimental impact on central nervous system. In particular, they may damage neuronal structure and function leading to deficits of neuroplasticity, the ability of nervous system to perceive, respond and adapt to external or internal stimuli. In search of the mechanisms by which pro-inflammatory cytokines may affect this crucial brain capability, we will discuss one of the most interesting hypotheses: the involvement of the neurotrophin brain-derived neurotrophic factor, which represents one of the major mediators of neuroplasticity.